Analisis Bauran Pemasaran di Rumah Sakit Pendidikan Universitas Hasanuddin - Sabran Sabran; Rini Anggraeni (Puslitbang Sinergis Asa Professional, 2019)
Nowadys, hospital is facing of global competiton era in every field. More or less of new patient is one of the problem of hospital. as a new hospital that has a marketing unit and will develop more of excellent service programs, hospital have to do evaluation of mix marketing programs that have implementated. the purpose of this study is. The kind of this study was a descriptive study with qualytatif approach by indeepth interview , observation and secondary data. There were eight respondent that choosen by purposive sampling. The results of this study were marketing process of hasanuddin university hospital was still has not a pattern yet, just promotion. Service price was base on unit cost of every installation. Then, easy to find outpatient installation because it was at the first floor, the kind of promotion media were brochure, sticker, magazine, website and company visitation. There was hospital funding for training to develop of human resources ability, admission for service easily, prepare of facilities by priority scale. The conclusion of this study was all of marketing mix have attentioned by hospital in making of marketing program.But also have to optimalisation of another product that still has not favorite yet and increase of promotion by electronic or mass media.